2016
DOI: 10.3389/fpsyg.2016.00209
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Difficulties in Perception of Tashlhiyt Berber Consonant Quantity Contrasts by Native Tashlhiyt Listeners vs. Berber-Naïve French Listeners

Abstract: In a discrimination experiment on several Tashlhiyt Berber singleton-geminate contrasts, we find that French listeners encounter substantial difficulty compared to native speakers. Native listeners of Tashlhiyt perform near ceiling level on all contrasts. French listeners perform better on final contrasts such as fit-fitt than initial contrasts such as bi-bbi or sir-ssir. That is, French listeners are more sensitive to silent closure duration in word-final voiceless stops than to either voiced murmur or fricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Cross-language perception has also been used to understand how language experience can be leveraged from an L1 to support the perception of typologically rarer sound contrasts in a non-native language. Relevantly, one study examined discrimination of the singleton-geminate contrast across different word positions (initial vs. final) in Tashlhiyt by naive listeners (whose L1 was French) (Hallé, Ridouane, & Best, 2016). They found that French listeners were better at discriminating between singleton and geminate segments when they were in word-final position, relative to word-initial position.…”
Section: Cross-language Perception Of Clear Speechmentioning
confidence: 99%
“…Cross-language perception has also been used to understand how language experience can be leveraged from an L1 to support the perception of typologically rarer sound contrasts in a non-native language. Relevantly, one study examined discrimination of the singleton-geminate contrast across different word positions (initial vs. final) in Tashlhiyt by naive listeners (whose L1 was French) (Hallé, Ridouane, & Best, 2016). They found that French listeners were better at discriminating between singleton and geminate segments when they were in word-final position, relative to word-initial position.…”
Section: Cross-language Perception Of Clear Speechmentioning
confidence: 99%
“…Research on foreign language (FL) speech learning focusing on non-segmental features such as length is increasing (e.g. Altmann et al, 2012 for German and Italian; McAllister et al, 2002 for Swedish; Meister and Meister, 2011 for Estonian; Ylinen et al, 2005 for Finnish; Hallé et al, 2016 for Tashlhiyt Berber). However, as pointed out in Altmann et al (2012) and Hallé et al (2016), most of it focuses on English (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Altmann et al, 2012 for German and Italian; McAllister et al, 2002 for Swedish; Meister and Meister, 2011 for Estonian; Ylinen et al, 2005 for Finnish; Hallé et al, 2016 for Tashlhiyt Berber). However, as pointed out in Altmann et al (2012) and Hallé et al (2016), most of it focuses on English (e.g. Han, 1992; Hayes-Harb, 2005) or Korean learners (e.g.…”
Section: Introductionmentioning
confidence: 99%